A Novel Radiotherapeutic Approach to Treat Bulky Metastases Even From Cutaneous Squamous Cell Carcinoma: Its Rationale and a Look at the Reliability of the Linear-Quadratic Model to Explain Its Radiobiological Effects - Ferini, Gianluca; Castorina, Paolo; Valenti, Vito; Illari, Salvatore Ivan; Sachpazidis, Ilias; Castorina, Luigi; Marrale, Maurizio; Pergolizzi, Stefano (Frontiers in Oncology, 2022)
Introduction Metastatic cutaneous squamous cell carcinoma (cSCC) is a very rare condition. The lack of definition of an oligometastatic subgroup means that there is no consensus for its treatment, unlike the mucosal head and neck counterpart. Like the latter, the cutaneous form is able to develop bulky tumor masses. When this happens, the classic care approach is just for palliative intent due to a likely unfavorable benefit–risk balance typical of aggressive treatments. Here we proposed a novel radiotherapy (RT) technique to treat bulky metastases from cSCC in the context of an overall limited tumor burden and tried to explain its clinical outcome by the currently available mathematical radiobiological and ad hoc developed models. Methods We treated a case of facial cSCC with three metastases: two of them by classic stereotactic RT and the other by lattice RT supported by metabolic imaging (18F-FDG PET) due to its excessively large dimensions. For the latter lesion, we compared four treatment plans with different RT techniques in order to define the best approach in terms of normal tissue complication probability (NTCP) and tumor control probability (TCP). Moreover, we developed an ad hoc mathematical radiobiological model that could fit better with the characteristics of heterogeneity of this bulky metastasis for which, indeed, a segmentation of normoxic, hypoxic, and necrotic subvolumes might have been assumed. Results We observed a clinical complete response in all three disease sites; the bulky metastasis actually regressed more rapidly than the other two treated by stereotactic RT. For the large lesion, NTCP predictions were good for all four different plans but even significantly better for the lattice RT plan. Neither the classic TCP nor the ad hoc developed radiobiological models could be totally adequate to explain the reported outcome. This finding might support a key role of the host immune system. Conclusions PET-guided lattice RT might be safe and effective for the treatment of bulky lesions from cSCC. There might be some need for complex mathematical radiobiological models that are able to take into account any immune system’s role in order to explain the possible mechanisms of the tumor response to radiation and the relevant key points to enhance it.